Intelligent knowledge management in medical applications - Wan Ishak, Wan Hussain; Siraj, Fadzilah; Othman, Abu Talib (2001)
Current practice for medical retrieval system involves large amount of papers as most patients' data are recorded on paper. Such a practice is not practical since patients' records are manually managed. Electronic database system inevitably increases the practicality and usability of patients' records. However, most of the medical systems developed are stand-alone applications, where each hospital has its own database system to store patients and patients-disease information. Problems arise when the patients consult another hospital or department for treatments. In some cases, medical therapy could give side effects to those that are allergic to certain medicines or drugs. Thus it is vital to provide a centralized database system that can assist doctors in diagnosing their patients' conditions. This paper proposes a web-based model for storing medical records. The knowledge-based technology (Artificial Intelligence) is incorporated in the model for diagnosing and prediction purposes. The importance of centralized database system and the importance of collaboration between medical practitioners in managing and providing a better health care to the public are also discussed.